2020
DOI: 10.1007/s40808-020-00965-w
|View full text |Cite
|
Sign up to set email alerts
|

Delineating changes in soil erosion risk zones using RUSLE model based on confusion matrix for the Urmodi river watershed, Maharashtra, India

Abstract: Soil loss by water erosion is a common type of land degradation issue in the hilly regions of the world. The present study investigates the soil erosion risk due to change in Land Use Land Cover (LULC) brought in by the construction of dam in a hilly watershed of the River Urmodi embracing Kaas Plateau, a world heritage site. The Revised Universal Soil Loss Equation (RUSLE) model was used with change detection analysis for soil erosion estimation. Thematic layers required for the computation of factors require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 31 publications
0
6
1
1
Order By: Relevance
“…It was also demonstrated that about 44.9 % of the study area fell under very high soil erosion risk, while high-probability zones covered 42.9% of the study areas (Figure 11). Compared with an earlier study [63] in the Urmodi river watershed (India), a significant output regarding increased conversion was obtained from very slight to very severe risk zone; research concluded the existence of extensive variation in very severe soil vulnerable risk zones over the study period. Overall, the findings of this study and other studies carried out in Rwanda and east African regions similar to results reported by Karamage [30,62], which seem to overestimate soil loss rates.…”
Section: Estimation Of Soil Loss and Probability Zonescontrasting
confidence: 66%
“…It was also demonstrated that about 44.9 % of the study area fell under very high soil erosion risk, while high-probability zones covered 42.9% of the study areas (Figure 11). Compared with an earlier study [63] in the Urmodi river watershed (India), a significant output regarding increased conversion was obtained from very slight to very severe risk zone; research concluded the existence of extensive variation in very severe soil vulnerable risk zones over the study period. Overall, the findings of this study and other studies carried out in Rwanda and east African regions similar to results reported by Karamage [30,62], which seem to overestimate soil loss rates.…”
Section: Estimation Of Soil Loss and Probability Zonescontrasting
confidence: 66%
“…It is a method for classifying the predicted values, namely the matching degree between the predicted values of the model to be trained on the test set and the real values on the test set. When the predicted value is equal to the true value, the matrix attains the correct classification that is located on the diagonal of the matrix, and non-diagonal elements represent the wrong classification [ 30 , 31 ].…”
Section: Screening and Function Prediction Model Of Degs Based On Dee...mentioning
confidence: 99%
“…In addition, the confusion matrix is a prominent way to analyze data and resolve problems that require classification [43,44]. The primary diagonal line displays the total number of classes correctly predicted by the intelligent system.…”
Section: Accuracymentioning
confidence: 99%